Improvements in the determination of attogram-sized 231Pa in dissolved and particulate fractions of seawater via multi-collector inductively coupled plasma mass spectrometry - Zhang, Pu; Lu, Yanbin; Zhang, Zhe; Edwards, Richard Lawrence; Anderson, Robert; Lam, Phoebe (Progress in earth and planetary science, 2023)
A technique is developed to quantify the ultra-trace 231 Pa (35–3904 ag) concentration in seawater using multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS). The method is a modification of the process developed by Shen et al. (Anal Chem 75(5):1075–1079, 2003. https://doi.org/10.1021/ac026247r ) and extends it to the application of very low levels of actinides, and the 35 ag 231 Pa can be measured with a precision of 15%. The total process blank for the water column was 0.02 ag/g, while the values of the large and small particles were ~ 30 ag/g. The ionization efficiency (ions generated/atom loaded) varies from 0.7 to 2.4%. The measurement time is 2–5 min. The amount of 231 Pa needed to produce 231 Pa data with an uncertainty of ± 0.8–15% is 35–3904 ag (~ 0.9 × 10 5 to 10 × 10 6 atoms). Replicate measurements of known standards and seawater samples demonstrate that the analytical precision approximates that expected from counting statistics, and that based on detection limits of 52 ag, 55 ag, and 28 ag, protactinium can be detected in a minimum seawater sample size of ~ 2.6 L for small suspended particulate matter (> 0.8 μm and < 51 μm), ~ 3.0 L for large suspended particulate matter (> 51 μm), and ~ 56 mL for filtered (< 0.45 μm) seawater. The concentration of 231 Pa (several attograms per liter) can be determined with an uncertainty of ± 2–8% (2 σ ) for suspended particulate matter filtered from ~ 60 L of seawater. For the dissolved fraction, ~ 1 L of seawater yields 231 Pa measurements with a precision of 0.8–10%. The sample size requirements are several orders of magnitude less than traditional decay-counting techniques, and the precision is better than that previously reported for ICP-MS techniques. Our technique can also be applied to other environmental samples, including river, lake, and cave water samples.